The Global AIMs Nano set: A 31-plex SNaPshot assay of ancestry-informative SNPs. (May 2016) - de la Puente, M.; Santos, C.; Fondevila, M.; Manzo, L.; Carracedo, Á.; Lareu, M.V.; Phillips, C.
Graphical abstract: Highlights: A 31-plex AIM-SNP set was assembled from the most differentiated markers in the Global forensic ancestry panel. The SNPs extend SNaPshot-based population differentiations to Native Americans and Oceanians. SNPs preserve balanced population-specific Divergence, reducing estimation bias of individual co-ancestry. Assessments of the assay's ability to type degraded or low level DNA indicate good sensitivity for routine forensic use. The SNaPshot assay gives a compact but powerful multiplex to infer ancestry for labs yet to adopt massively parallel sequencing. Abstract: A 31-plex SNaPshot assay, named 'Global AIMs Nano', has been developed by reassembling the most differentiated markers of the EUROFORGEN Global AIM-SNP set. The SNPs include three tri-allelic loci and were selected with the goal of maintaining a balanced differentiation of: Africans, Europeans, East Asians, Oceanians and Native Americans. The Global AIMs Nano SNP set provides higher divergence between each of the five continental population groups than previous small-scale AIM sets developed for forensic ancestry analysis with SNaPshot. Both of these characteristics minimise potential bias when estimating co-ancestry proportions in individuals with admixed ancestry; more likely to be observed when using markers disproportionately informative for only certain population group comparisons. The optimised multiplex is designed to be easily implemented using standard capillary electrophoresis regimes and has been used to successfully genotype challenging forensic samples from highly degraded material with low level DNA. The ancestry predictive performance of the Global AIMs Nano set has been evaluated by the analysis of samples previously characterised with larger AIM sets.